Simulation and Test of Key Decorticating Components of Spiral Ramie Decorticator - Wenlong Zheng; Lan Ma; Jiajie Liu; Bo Yan; Yiping Duan; Sixun Chen; Jiangnan Lyu; Wei Xiang (Agronomy)
Ramie is a valuable natural fiber resource. The fabric made of ramie fiber has distinctive natural characteristics, and its products are widely favored in the international market. Because the cellulose fiber in ramie is closely adhered by a viscous material composed of pectin, hemicellulose, and lignin, mechanical stripping and processing is needed to obtain primary ramie fiber for downstream use. To address the production challenges posed by high labor intensity and the scarcity of small, direct-feeding ramie decorticators in hilly and mountainous regions, this study designed and optimized a spiral ramie decortication component that integrated functions of ramie stalk crushing, xylem removal, outer shell scraping, and phloem separating and throwing. The three-dimensional model of the ramie stripping component was crafted with SolidWorks software, and subsequent modal analysis and dynamic simulation studies were conducted using Abaqus software. The Box–Behnken experimental design method was used to construct a mathematical model describing the effects of the decorticating drum rotation speed and the decorticating gap on the fiber percentage of fresh stalk, and the optimal operating parameters were determined accordingly. The research findings indicated that the component’s initial ten natural frequencies span from 234.41 to 431.70 Hz, which do not overlap with the external excitation frequencies, thus ensuring that no resonance phenomenon occurs during the operation process, meeting the design requirements for the ramie decortication operation. Under dynamic load conditions, the ramie decorticator can efficiently perform the task of ramie fiber decortication, and the stress and strain experienced by the device meet the established design specifications; by optimizing operating parameters, the optimal operating conditions were determined to be the speed of feeding and crushing parts (SFCP) of 100 r/min, the speed of separating and throwing parts (SSTP) of 400 r/min, the gap of feeding and crushing parts (GFCP) of 8 mm, and the gap of separating and throwing parts (GSTP) of 0 mm. Experimental results indicated that under this optimal parameter combination, the fiber percentage of fresh stalk of the spiral ramie decorticator can reach 5.03%, with a relative error of less than 3% compared to the theoretical model prediction value, thus confirming the accuracy of the model prediction. This study establishes a robust technical basis for the development of a convenient decortication technology for ramie fibers. However, this technique is more suitable for small growers, especially in hilly areas, to achieve large-scale applications, schemes must be reevaluated based on production efficiency.